2006
DOI: 10.1093/intimm/dxl103
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of vasoactive intestinal peptide receptors in T lymphocytes and aberrant Th1 immunity in multiple sclerosis

Abstract: Vasoactive intestinal peptide (VIP) has a unique property of regulating T(h)1 and T(h)2 immunity of CD4+ T cells. In this study, we demonstrated, for the first time, that differential expression of VIP receptors and a compensatory mechanism directly affect the responsiveness of CD4+ T cells and their T(h)1 and T(h)2 properties to VIP. The expression of VIP receptor-1 (VPAC1) and VPAC2 in CD4+ T cells changed reciprocally in the context of the activation state. In activated CD4+ T cells of healthy individuals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…This is the first report to describe a genetic association of VIP or of its 2 VIP receptors with any autoimmune disorder. Reduced levels of VIP and altered expression of VPAC 2 in T cells from patients with multiple sclerosis were recently reported (9); however, results of 2 different studies have failed to support the notion of genetic polymorphisms within the VIP and VPAC 2 genes in that disease (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first report to describe a genetic association of VIP or of its 2 VIP receptors with any autoimmune disorder. Reduced levels of VIP and altered expression of VPAC 2 in T cells from patients with multiple sclerosis were recently reported (9); however, results of 2 different studies have failed to support the notion of genetic polymorphisms within the VIP and VPAC 2 genes in that disease (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have been undertaken in an effort to correlate altered VIP levels, presence of VIP autoantibodies, or VIP genetic variants with severity and incidence of autoimmunity, no association has been conclusively demonstrated (6)(7)(8)(9). We hypothesized that the exacerbated inflammatory autoimmune response in RA might result directly from altered expression and/or signaling of VIP receptors in immune cells.…”
mentioning
confidence: 99%
“…For example, it has been reported that patients with multiple sclerosis (MS) have reduced VIP immunoreactivity in the cerebral spinal fluid (12). Moreover, Th cells isolated from patients with MS have an altered profile of VIP receptors, and are resistant to an action of VIP to promote a positive Th2/Th1 balance (13). In contrast, an up-regulation of VIP levels was observed in the serum and joints of mice with collagen-induced arthritis (14) and in the serum and peritoneal suspensions of mice injected with LPS (8).…”
mentioning
confidence: 99%
“…This compromise to VPAC2 in MS patients may also occur at the molecular level where mRNA expression levels of VPACR2 are down regulated. Additionally, the formation of the VIP ligand receptor complex stimulates cAMP/PKA downstream effects which ultimately dampen IFN-and stimulates the generation of GATA3 (Sun et al, 2006). This in effect increases the expression of Th2 immune cells.…”
Section: Multiple Sclerosismentioning
confidence: 99%